2013
DOI: 10.2478/s11535-013-0199-9
|View full text |Cite
|
Sign up to set email alerts
|

Winter diet analysis in Rhinolophus euryale (Chiroptera)

Abstract: We investigated the winter food of Mediterranean horseshoe bats (Rhinolophus euryale) in four winter cave roosts in southern Slovakia and northern Hungary and investigated the relationship between food and ambient temperature. The bats were active during the whole winter period and they produced excrement throughout the entire hibernation period, even when outside temperatures dropped below zero. The guano was in two forms, containing (1) prey items and (2) non-prey items. The identifiable items belonged to le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Geochemical studies of cave guano, including studies using stable isotopes in particular, can provide paleoecological (relative abundance of C 3 -, C 4 -or CAM-type plants, vegetation changes, feeding behaviour of bats) and paleoclimate (precipitation) records (Des Marais et al, 1980;Mizutani et al, 1992a;McFarlane et al, 2002;Bird et al, 2007;Wurster et al, 2007;Onac et al, 2014Onac et al, , 2015. This work on cave paleoclimatic studies, builds on previous paleoenvironmental and paleoclimatic reconstructions using carbon isotopic composition of insect chitin in non-cave settings Miller, 1991;Gr€ ocke et al, 2006).…”
Section: Introductionmentioning
confidence: 95%
“…Geochemical studies of cave guano, including studies using stable isotopes in particular, can provide paleoecological (relative abundance of C 3 -, C 4 -or CAM-type plants, vegetation changes, feeding behaviour of bats) and paleoclimate (precipitation) records (Des Marais et al, 1980;Mizutani et al, 1992a;McFarlane et al, 2002;Bird et al, 2007;Wurster et al, 2007;Onac et al, 2014Onac et al, , 2015. This work on cave paleoclimatic studies, builds on previous paleoenvironmental and paleoclimatic reconstructions using carbon isotopic composition of insect chitin in non-cave settings Miller, 1991;Gr€ ocke et al, 2006).…”
Section: Introductionmentioning
confidence: 95%
“…[19] and noctules ( Nyctalus noctula ) [20], and a single Natterer’s bat ( Myotis nattereri ) was radio tracked foraging outside of the hibernaculum over ten winter nights in the south of England [13]. Furthermore, studies on the winter diet of rhinolophid bats confirmed that these species feed throughout the winter in the United Kingdom [21,22] and continental Europe [23]. The majority of arousals [10,13] and peaks in subsequent activity [24,25] are synchronised around sunset, when insects will be most abundant [11,26].…”
Section: Introductionmentioning
confidence: 99%
“…We found that male individuals were generalists, while females were specialists, as they ate specific orders of insects that fit their energy demand in different reproductive stages. Male individuals fed on any insects that were abundant during that season and were observed to fly more actively than female individuals ( Miková et al, 2013 ) due to energy demand. In this study, pregnant females were recorded to feed mostly on Coleoptera.…”
Section: Discussionmentioning
confidence: 99%